2015
DOI: 10.1111/ejn.12850
|View full text |Cite
|
Sign up to set email alerts
|

Modulation in the mirror neuron system when action prediction is not satisfied

Abstract: The ability to understand competitive games is closely connected to the mirror neuron system (MNS). This network is activated not only when an action is performed, but also when it is observed. Apart from allowing the understanding of actions performed by others, the MNS has been implicated in predicting subsequent actions. However, the results concerning the modulation of this network by the final outcome of these predictions are contradictory. These contradictions may be related to the use of complex experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
3
2
0
Order By: Relevance
“…Wurm and colleagues (2014) showed that activity in several regions of the AON -in particular in the inferior frontal gyrus and occipitotemporal cortex -decreased as a function of goal predictability. These findings support the notion that the action observation network is modulated by action predictability (see also Plata Bello et al, 2015).…”
Section: Predictions In the Motor System: The Role Of Sensorimotor Ossupporting
confidence: 87%
See 1 more Smart Citation
“…Wurm and colleagues (2014) showed that activity in several regions of the AON -in particular in the inferior frontal gyrus and occipitotemporal cortex -decreased as a function of goal predictability. These findings support the notion that the action observation network is modulated by action predictability (see also Plata Bello et al, 2015).…”
Section: Predictions In the Motor System: The Role Of Sensorimotor Ossupporting
confidence: 87%
“…Moreover, our findings complement recent fMRI research suggesting that brain regions involved in action perception (i.e. premotor, parietal and occipitotemporal areas, often referred to as the action observation network (AON), see Cross et al, 2012;Cross, Kraemer, Hamilton, Kelley, & Grafton, 2009;Gazzola & Keysers, 2009;Schubotz, 2007) are modulated by action predictability (Plata Bello, Modroño, Marcano, & González-Mora, 2015;Wurm, Hrkać, Morikawa, & Schubotz, 2014). Wurm and colleagues (2014), for instance, assessed the processing of multi-step actions which were either characterized by the presence of an overarching action goal or not (see also .…”
Section: Predictions In the Motor System: The Role Of Sensorimotor Ossupporting
confidence: 81%
“…In the predictive coding framework contextual information or prior knowledge is able to guide the observer towards inferring the most likely intention of an observed movement even if sensory input is uncertain or lacking completely. This theory is supported by several studies showing that predictions regarding observed actions can modulate the mirror responses (Cross, Stadler, Parkinson, Schütz-Bosbach, & Prinz, 2013;Plata Bello, Modroño, Marcano, & González-Mora, 2015;Press, Weiskopf, & Kilner, 2012;Thioux & Keysers, 2015;Wurm & Schubotz, 2012. Our results show that grip specific facilitation of human M1 is consistent with this idea, suggesting that contextual cues activated top-down mechanisms which facilitated highly specific motor representations in M1.…”
Section: Combining Kinematic and Context Information During Action Obsupporting
confidence: 89%
“…This information activated per se frontal speech areas that are closely tied to the motor plan that has to be executed to produce the same speech movement [29]. The presentation of an incongruent visual stimuli would lead to different results [30].…”
Section: Discussionmentioning
confidence: 99%